2018
DOI: 10.2478/pielxxiw-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of pediatric nurses about Jehovah’s Witnesses refusal of blood transfusion for their child

Abstract: Introduction. Jehovah’s Witnesses absolutely refuse having blood transfusion performed. The situation is even more difficult when the refusal of blood transfusion concerns a child. Despite existing legal solutions, medical staff experiences value conflicts. Aim. To analyze the opinions of pediatric nurses about problems that may arise in case of Jehovah’s Witnesses refusal of blood transfusion for their child. Material and methods. Quantitative research was based on a diagnostic survey method. The variables we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…More than 83% of nurses in Lublin, Poland, claimed to have had contact with JW patients and more than half (50.02%) rejected JWs’ position concerning blood treatment, 44.23% admitting to having tried to persuade JW parents to change their minds and accept blood transfusions [ 70 ]. While 83% of anaesthesiologists, physicians and surgeons in France did not oppose the medical care of JWs, they remained committed to their primary focus: to save the patient, as long as it is not an end-of-life situation, and 67% admitted that in life and death situations, where there is a lack of alternative procedures, blood products should be administered [ 71 ]. Although German doctors stressed the importance of personal autonomy, they also referred to doctors’ consciences and their ethical professional obligations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than 83% of nurses in Lublin, Poland, claimed to have had contact with JW patients and more than half (50.02%) rejected JWs’ position concerning blood treatment, 44.23% admitting to having tried to persuade JW parents to change their minds and accept blood transfusions [ 70 ]. While 83% of anaesthesiologists, physicians and surgeons in France did not oppose the medical care of JWs, they remained committed to their primary focus: to save the patient, as long as it is not an end-of-life situation, and 67% admitted that in life and death situations, where there is a lack of alternative procedures, blood products should be administered [ 71 ]. Although German doctors stressed the importance of personal autonomy, they also referred to doctors’ consciences and their ethical professional obligations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research therefore shows that, while most NPs supported adult JW patients’ right to refuse a blood transfusion, they showed little understanding for such a decision and expressed resentment towards JWs’ stance. A study by Jakubowska et al [ 45 ] also showed that 50.02% of paediatric nurses in Lublin (eastern Poland) disagreed with JWs concerning blood treatment. Gouezec et al [ 46 ], on the other hand, demonstrated that, although French doctors do not oppose the medical care of JWs, the majority were somewhat lacking in their awareness of all the regulatory requirements, and remained committed to their primary focus: to save the patient, as long as it is not an end-of-life situation.…”
Section: Discussionmentioning
confidence: 99%